2014
DOI: 10.3897/compcytogen.v8i4.8813
|View full text |Cite
|
Sign up to set email alerts
|

First karyotype data on the family Myerslopiidae (Hemiptera, Auchenorrhyncha, Cicadomorpha)

Abstract: In the first cytogenetic study of the recently proposed family Myerslopiidae the male karyotype of Mapuchea chilensis (Nielson, 1996) was analyzed using conventional chromosome staining, AgNOR- and C-bandings, and fluorescence in situ hybridization (FISH) with 18S rDNA and (TTAGG)n telomeric probes. A karyotype of 2n = 16 + XY, NOR on a medium-sized pair of autosomes, subterminal location of C-heterochromatin, and presence of (TTAGG)n telomeric sequence were determined. Additionally, the male internal reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…Among Hemiptera, the ancestral motif is present in the suborder Sternorrhyncha (coccids and aphids with some exceptions) (Mohan et al 2011, Monti et al 2011, Novotná et al 2011), in several genera of Auchenorrhyncha (Frydrychová et al 2004, Maryańska-Nadachowska et al 2013, Golub et al 2014, Kuznetsova et al 2015a) and Coleorrhyncha (Kuznetsova et al 2015b) suborders. In the suborder Heteroptera, only two species of the basal infraorders Nepomorpha and Gerromorpha show the ancestral telomeric motif (Kuznetsova et al 2012, Mason et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among Hemiptera, the ancestral motif is present in the suborder Sternorrhyncha (coccids and aphids with some exceptions) (Mohan et al 2011, Monti et al 2011, Novotná et al 2011), in several genera of Auchenorrhyncha (Frydrychová et al 2004, Maryańska-Nadachowska et al 2013, Golub et al 2014, Kuznetsova et al 2015a) and Coleorrhyncha (Kuznetsova et al 2015b) suborders. In the suborder Heteroptera, only two species of the basal infraorders Nepomorpha and Gerromorpha show the ancestral telomeric motif (Kuznetsova et al 2012, Mason et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At present, telomeres and the major rDNA loci are the most widely documented chromosomal regions in insects, including the order Hemiptera (e.g. Blackman et al 2000, Manicardi et al 2002, Monti et al 2011a, b, Grozeva et al 2011, 2014, Panzera et al 2012, Chirino et al 2013, Maryańska-Nadachowska et al 2013, Pita et al 2013, Bardella et al 2013, Golub et al 2014, 2015, Kuznetsova et al 2012, 2015a). In addition, recent publications have shown that the number and chromosomal locations of the major rDNA multigene families are useful for the study of karyotype evolution in other insect groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this large hemipteran (= homopteran) group, FISH with rDNA and conserved insect telomeric (TTAGG) n repeats has so far been applied to 25 species, including 8 species of the genus Philaenus Stål, 1864 from the froghopper family Aphrophoridae (Maryańska-Nadachowska et al 2013, Kuznetsova et al 2015c); Mapuchea chilensis (Nielson, 1996) from the leafhopper family Myerslopiidae (Golub et al 2014); 5 species of the genus Alebra Fieber, 1872 from the leafhopper family Cicadellidae (Kuznetsova et al 2015b); and 11 species of the planthopper family Issidae (present paper). In addition, Frydrychová et al (2004) reported on telomeric sequences in Calligypona pellucida (Fabricius, 1794) from the planthopper family Delphacidae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A note on the myerslopiids karyotype and tests has already been published [15]. Here, I present ecological, behavioral, and anatomical observations to demonstrate that myerslopiids present no significant departures from cicadellids in their life history traits, but their Malpighian tubules have a different organization, not previously known among Hemiptera.…”
Section: Introductionmentioning
confidence: 93%